HUBUNGAN COPING MECHANISM DENGAN HASIL UJIAN AKHIR BLOK BASIC MEDICAL SCIENCE PADA MAHASISWA ANGKATAN 2016 - Ana Mariza; Lia Ayuningtias (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
Effect of nei–guan point (P6) acupressure on nausea and vomiting in women with hyperemesis gravidarum Background: Prevalence of emesis gravidarum issued by the explains that more than 80% of pregnant women in Indonesia experience excessive nausea and vomiting. the incidence of gravidarum emesis cases is 0.8 to 32 cases per 1,000 pregnancies. Therefore, the treatment of labor pain is necessary mother of birth.. While in the year 2017 period January-December as many as 56 cases of hyperemesis gravidarum of 132 visits and 26 pregnant women (46.43%) received treatment and medical treatment.Purpose: Knowing the effect of giving acupressure point P6 to nausea and vomiting in pregnant women TM I in BPM Wirahayu Panjang Year 2018.Methods: Quantitative research type, experimental quasi research design with one group pretest - posttest design approach. The number of population and samples is 30 people, purposive sampling technique samples. Data Analysis using t-test.Results: Showed vomiting before being given intervention Mean 10.53 Min 9 Max 13 and Standard Deviation 1.408 and Standard Error 0.257, after being given acupressure Mean 7.30 Min 5 Max 10 and Standard Deviation 1,317 and Standard Error 0.240. Statistical test results obtained P-value = 0.000 means that there is an effect of p6 point acupressure on nausea and vomiting in pregnant women TM I at BPM Wirahayu Panjang in 2018.Conclusion: Acupressure stimulates the regulatory system and activates endocrine and neurological mechanisms, by stimulating the hypothalamus to removing endorphins which give a sense of relaxation.Suggestions: are used as input in providing information about nausea and vomiting, understanding, handling and impact if nausea vomiting is allowed, besides providing benefits and information resources for mothers about handling nausea and vomiting using acupressure massage in daily life Keywords: Nei–guan point (P6); Acupressure; Nausea; Vomiting; Women; Hyperemesis; Gravidarum Pendahuluan: Prevalensi emesis gravidarum lebih dari 80% wanita hamil di Indonesia mengalami mual dan muntah yang berlebihan. Insidensi terjadinya kasus emesis gravidarum sebesar 0,8 sampai 32 kasus per 1.000 kehamilan. Oleh sebab itu penanganan mual muntah pada kehamilan sangat perlu dilakukan terhadap ibu hamil TM 1. Sedangkan pada tahun 2017 periode Januari-Desember sebanyak 56 kasus hyperemesis gravidarum dari 132 kunjungan kehamilan dan 26 orang ibu (46.43%) mendapat perawatan dan tindakan medis.Tujuan: Diketahui pengaruh pemberian akupresure titik P6 terhadap mual dan muntah pada ibu hamil TM I di BPM Wirahayu Panjang Tahun 2018.Metode: Jenis penelitian kuantitatif, rancangan penelitian quasi eksperimental dengan pendekatan one group pretest – posttest design. Jumlah populasi 120 orang ibu hamil dan sampel sebanyak 30 orang, teknik sampel purposive sampling. Analisa Data menggunakan uji t-test.Hasil: Menunjukan muntah sebelum diberi intervensi Mean 10.53 Min 9 Max 13 danStandar Deviasi 1.408 dan Standar Eror 0.257, sesudah diberi akupresur Mean 7.30 Min 5 Max 10 dan Standar Deviasi 1.317 dan Standar Eror 0.240. Hasil uji statistik didapatkan nilai P-value = 0.000 artinya terdapat Pengaruh pemberian akupresure titik p6 terhadap mual dan muntah pada ibu hamil TM I di BPM Wirahayu Panjang Tahun 2018.Simpulan: Akupresur menstimulasi system regulasi serta mengaktifkan mekanisme endokrin dan neurologi, dengan cara merangsang kerja hipotalamus untuk mengeluarkan zat endorphin yang memberikan rasa rileks.Saran: Sebagai masukan dalam memberikan informasi tentang mual dan muntah, pengertian, penanganan dan dampak jika mual muntah dibiarkan, selain itu memberikan manfaat dan sumber informasi bagi ibu tentang penanganan mual muntah menggunakan pijat akupresur dalam kehidupan sehari-hari